Humour loss in the Indonesian translation of Harry Potter and the Sorcerer's Stone - Yuliasri, Issy; Allen, Pamela (Universitas Pendidikan Indonesia, 2019)
This article explores the preservation of humour in the Indonesian translation of Harry Potter and the Sorcerer’s Stone. Through the use of questionnaires completed by young readers aged 12-15 years old, we examine whether passages in the novel that are deemed humorous in the English original are also perceived as such by Indonesian readers. Our findings reveal the complexity of translating linguistic and culturally-specific humour in a novel. We conclude that the Indonesian translator of Harry Potter and the Sorcerer’s Stone adopted an interpretative-communicative method of translation. In doing so, some compromises were made, particularly, through simplification, which frequently resulted in humour loss.